Developing Listening Materials for Information and Enjoyment Based on Local Wisdom - Sriwahyuni, Sriwahyuni; Hartiningsari, Dwi Putri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aimed to develop listening materials for information and enjoyment based on local wisdom. The research employed an RD approach using a pre-experimental design with a One-Group Pre-test Post-test model. The participants were second-semester students of the English Language Education Department at STKIP PGRI Trenggalek in the 2024/2025 academic year. The research procedures included needs analysis, reviewing relevant educational theories, developing the product, expert validation, and field testing. Data were collected through questionnaires and tests, then analysed descriptively and statistically. The needs analysis results showed a score of 78 percent, indicating that students agreed with and supported the development of the material. Field testing demonstrated a significant improvement in students’ scores from the pre-test to the post test after using the developed materials. These findings suggest that the developed local-wisdom-based listening materials contribute positively to improving students’ English listening skills.